Parliament, power and patronage, the career of Speaker William Conolly, 1662-1729 - Walsh, Patrick (Trinity College Dublin, 2007)
The aim of this project is not to write a biography of Conolly but rather to examine particular facets of his career. His political career has previously been outlined in the political histories of the period and does not form a major part of my project. Instead my project focuses on other neglected aspects of his career including the amassment of his fortune and the relationship between his land dealings and his legal career to his later career. I have also examined his career in the revenue service, which began with his appointment as Collector, Customer and Receiver for Londonderry and Coleraine in 1695 and culminated in his dominance of the revenue board in the 1720s. The links between his political and revenue careers are also explored. This aspect of his career is of particular importance as later speakers of the House of Commons followed his example and held office at the revenue board as well. I have also attempted to integrate his contributions to the building of Castletown and the houses of parliament into the wider concerns of his career. My study concludes with a broad discussion of Conolly's career, examining how these disparate elements came together to bring about his dominant role in Irish life. My research has been based in a wide range of archival and printed, sources found in libraries and archives, both in Ireland and in Britain.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: William Conolly, Speaker of the House of Commons; Seventeenth-century Irish History; Eighteenth-century Irish history